Efficient preparation process of high modulus graphene oxide / natural rubber uniformly cured solid load-bearing tire
By using high-modulus graphene oxide/natural rubber composite materials in solid rubber tires, and adopting specific process steps and step-by-step vulcanization processes, the problem that existing tires are prone to bursting and chipping under high loads is solved, and the problem is significantly improved. improve the mechanical properties and service life of the tire.
Patent Information
- Application Number
- CN202410067427.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-17
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-01-17
AI Technical Summary
Existing solid rubber tires are prone to high-temperature bursts, collapse and blocking when subjected to shear, tension and torsion, and have poor cutting resistance, which cannot meet the high-performance needs of heavy-duty vehicles.
High modulus graphene oxide/natural rubber composite material is used, and through specific process steps, including ultrasonic dispersion, internal mixing, open refining, vulcanization, etc., a "sandwich structure" compound rubber sheet is prepared. Combined with the step-by-step vulcanization process, Improve tire vulcanization uniformity and mechanical properties.
Significantly improve the hardness, modulus, fatigue resistance and tear resistance of the tire, reduce the dynamic heat generation value and extend the service life of the tire.
Smart Images

Figure CN118024645B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of graphene and functional natural rubber composite materials, and in particular to an efficient preparation process for a high modulus graphene oxide / natural rubber uniformly cured solid load-bearing tire. Background Art
[0002] Rubber is an important strategic material with unique viscoelasticity and is widely used in industry and defense. Natural rubber (NR) has excellent elasticity, wear resistance, anti-aging and corrosion resistance, making it one of the ideal materials for preparing solid rubber tires. However, due to its low hardness, NR deforms greatly when subjected to external forces. On the one hand, it cannot carry heavy engineering equipment, and on the other hand, it is very easy to produce microcracks, leading to failure and thus reducing the service life of the tire. The commonly used method to solve this problem is to add inorganic fillers such as carbon black to improve the mechanical properties of NR composites. However, with the continuous advancement of science and technology, more stringent requirements are placed on the performance of rubber composites.
[0003] In order to further improve the performance of NR, nanoparticles such as ceramic particles, nanodiamonds, carbon nanotubes and graphene (GE) have become ideal fillers for reinforcing rubber matrices due to their small size and large specific surface area. Among them, GE and its derivatives are considered to be the most ideal fillers for NR composites and are often used to improve mechanical, electrical, thermal and chemical properties. As an important representative of GE derivatives, graphene oxide (GO) is rich in oxygen-containing groups such as hydroxyl, epoxy, carboxyl and carbonyl groups on its surface, which give it hydrophilicity and make it easy to disperse evenly in natural latex. At the same time, these oxygen functional groups are conducive to improving the interfacial interaction between GO and the NR matrix. Therefore, it is widely used to reinforce modified rubber, thereby improving the safety, durability and performance of molded solid tires.
[0004] High modulus rubber composites are widely used in rubber products, such as tire apex, automobile transmission belts, road wheels, etc. As heavy vehicles develop towards heavy loads and high speeds, the shear, tension, compression, and torsion of the road wheel rubber body are more intense. Therefore, during the driving of heavy vehicles, the temperature rise of solid rubber tires is obvious, which is prone to high-temperature bursting, chipping, and falling off. Especially when driving on complex roads, solid rubber tires have poor cutting resistance. Therefore, solid tire tread rubber must have high modulus, low dynamic heat generation, high fatigue resistance, high strength, tear resistance and other comprehensive excellent properties to meet the above requirements.
[0005] The vulcanization degree of different parts of solid rubber tires and the determination of the vulcanization time of thick products have always been of great concern. Since rubber is a poor conductor of heat, as the thickness of the product increases, the rubber in various places cannot be heated evenly and synchronously, resulting in the internal and external temperature gradient increasing with the increase in the thickness of the rubber layer, causing the vulcanization degree of the internal and external rubber to be significantly different at the same vulcanization time. Therefore, to determine the vulcanization process parameters, it is first necessary to ensure that the rubber in each part is fully vulcanized, that is, there is no lack of vulcanization inside and no over-vulcanization outside. Under this premise, it is also necessary to determine the shortest vulcanization time to improve production efficiency while ensuring product quality. Summary of the invention
[0006] The present invention overcomes the deficiencies of the prior art and provides an efficient preparation process for a high modulus graphene oxide / natural rubber uniformly cured solid load-bearing tire.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: an efficient preparation process of high modulus graphene oxide / natural rubber and its uniformly cured solid load-bearing tire, wherein the high modulus graphene oxide / natural rubber is made of the following raw materials in the following mass proportions:
[0008] 100 parts of natural rubber, 40-120 parts of carbon black (CB), 0.5-5 parts of graphene oxide, 1-20 parts of activator, 1-20 parts of softener, 1-10 parts of antioxidant, 1-10 parts of antioxidant, 1-20 parts of vulcanization accelerator, 1-20 parts of vulcanizing agent, 1-20 parts of interface modifier;
[0009] The preparation process comprises the following steps:
[0010] (1) adding deionized water to graphene oxide slurry, and obtaining a uniform aqueous dispersion of graphene oxide by ultrasonic dispersion;
[0011] (2) adding the graphene oxide uniform aqueous dispersion obtained in step (1) to natural rubber latex, and stirring and mixing them thoroughly to obtain a uniformly dispersed mixed emulsion; adding a flocculant to break the emulsion to obtain raw rubber, washing, dehydrating, and drying to obtain a graphene oxide / natural rubber masterbatch;
[0012] (3) placing the graphene oxide / natural rubber masterbatch obtained in step (2) in an internal mixer for internal mixing, adding carbon black, interfacial modifier, antioxidant, antioxidant, vulcanization accelerator, activator and softener in sequence, discharging the rubber after internal mixing time A, cooling to room temperature, and then mixing the rubber on an open mixer for time A, adding a vulcanizing agent, mixing evenly, and thinning until there are no bubbles in the rubber to obtain a high modulus graphene oxide / carbon black / natural rubber mixed rubber and pressing it into a film;
[0013] (4) placing the graphene oxide / natural rubber masterbatch obtained in step (2) in an internal mixer for internal mixing, adding carbon black, interfacial modifier, antioxidant, antioxidant, vulcanization accelerator, activator and softener in sequence, discharging the rubber after internal mixing time B, cooling to room temperature, and then mixing the rubber on an open mixer for time B, adding a vulcanizing agent, mixing evenly, and thinning until there are no bubbles in the rubber to obtain a high-viscosity graphene oxide / carbon black / natural rubber mixed rubber and pressing it into a film;
[0014] (5) placing the high modulus graphene oxide / carbon black / natural rubber mixed rubber sheet obtained in step (3) between the upper and lower high viscosity graphene oxide / carbon black / natural rubber mixed rubber sheets obtained in step (4) to form a "sandwich structure" mixed rubber, and after standing for a certain period of time, forming a "sandwich structure" rubber strip with a width smaller than the width of the metal hub;
[0015] (6) applying adhesive to the surface of the metal hub of the road wheel and drying it, and then wrapping the "sandwich structure" rubber strip prepared in step (5) around the surface of the metal hub, with the wrapping thickness being the designed thickness of the rubber layer of the road wheel;
[0016] (7) The metal wheel hub wrapped with the "sandwich structure" rubber strip obtained in step (6) is placed in a road wheel mold and vulcanized in steps, the first step is vulcanized at high temperature for time C, and the second step is vulcanized at low temperature for time D, to obtain a high modulus graphene oxide / natural rubber uniformly cured solid load-bearing tire. As a further improvement of the technical solution of the present invention, the interface modifier is selected from at least one of Si69, Si75, Si75-ES and Si264.
[0017] As a further improvement of the technical solution of the present invention, the vulcanization accelerator is N-tert-butyl-2-benzothiazole sulfenamide, N-cyclohexyl-2-benzothiazole sulfenamide or N-(diethylene oxide)-2-benzothiazole sulfenamide; the antioxidant is 2,6-di-tert-butyl-4-methylphenol, 2,2,4-trimethyl-1,2-dihydroquinoline polymer or 2-thiol benzoimidazole; the antioxidant is N-(1-methylisopentyl)-N'-phenyl-p-phenylenediamine, p-phenylaniline or dilauryl dipropionate sulfide; the activator is zinc gluconate, zinc oxide or magnesium oxide; the softener is stearic acid, dibutyl titanate or dioctyl adipate; and the vulcanizing agent is sulfur or sulfur monochloride.
[0018] As a further improvement of the technical solution of the present invention, in step (1), the power of the ultrasonic dispersion is 100 to 300 W, the time of the ultrasonic dispersion is 5 to 20 min, and the concentration of the obtained graphene oxide uniform aqueous dispersion is 2 to 6 mg / mL.
[0019] As a further improvement of the technical solution of the present invention, in step (3), the mixing temperature in the internal mixer is 110-120° C., and the mixing time A is 5-12 min; the mixing temperature in the open mixer is 50-80° C., and the mixing time A is 6-15 min; the mass ratio of the graphene oxide in step (1), the rubber solids in the natural latex in step (2) and the carbon black, interfacial modifier, antioxidant, antioxidant, vulcanization accelerator, activator, softener and vulcanizer in step (3) is 0.5-5:100:40-120:1-20:1-10:1-10:1-20:1-20:1-20:1-20:1-20.
[0020] As a further improvement of the technical solution of the present invention, in step (4), the mixing temperature in the internal mixer is 110-120° C., and the mixing time B is 5-12 min; the mixing temperature of the open mixer is 50-80° C., and the mixing time B is 15-25 min; the mass ratio of the graphene oxide in step (1), the rubber solids in the natural latex in step (2) and the carbon black, interfacial modifier, antioxidant, antioxidant, vulcanization accelerator, activator, softener and vulcanizer in step (4) is 0.5-5:100:40-120:1-20:1-10:1-10:1-20:1-20:1-20:1-20:1-20.
[0021] As a further improvement of the technical solution of the present invention, in step (5), the thickness of the middle layer of high modulus mixed film of the "sandwich structure" mixed film is 3 to 6 mm, the thickness of the upper layer of high viscosity mixed film is 0.3 to 1 mm, and the thickness of the lower layer of high viscosity mixed film is 0.3 to 1 mm; the stop time is 20 to 30 hours.
[0022] As a further improvement of the technical solution of the present invention, in step (6), the adhesive is a general adhesive selected from at least one of Chemlok 6125, Chemlok 205 and Chemlok 6150.
[0023] As a further improvement of the technical solution of the present invention, in step (7), the vulcanization pressure is 10-25 MPa, the first step vulcanization temperature is 150-170°C, the vulcanization time C is 2-6 min, the second step vulcanization temperature is 140-150°C, and the vulcanization time D is 10-30 min.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1) In the present invention, the two reinforcing fillers of carbon black and graphene are used together with an in-situ interface modification process to improve their dispersibility in rubber and their interface interaction with rubber, thereby improving the hardness and mechanical properties of the composite material while making the molded tire have a low dynamic heat generation value during driving, thereby slowing down the aging failure of the load-bearing tire.
[0026] 2) The interface modifier in the present invention can play two roles. First, it can improve the dispersibility of carbon black and GO in the NR matrix, while the dispersibility of reinforcing fillers in rubber is crucial to improving the performance of composite materials. Silane coupling agents can improve the properties of the surfaces of carbon black and GO, improve their compatibility with NR, and thus enhance the interfacial interaction with rubber; second, the interface modifier can chemically react with the NR matrix to form a vulcanized cross-linking network, improve the bonding strength between the filler and the rubber, and improve the mechanical properties and durability of the composite material.
[0027] 3) Compared with other tire preparation processes, the present invention adopts an efficient and industrially convenient aqueous phase synergistic coagulation process to prepare GO / NR masterbatch with good dispersion effect, further prepares GO / CB / NR mixed rubber by mechanical blending, and finally prepares a road wheel solid tire by vulcanization process. Each of the above steps can be prepared by conventional processes; the materials involved are green and environmentally friendly, and the price is low; the instruments and equipment are simple to operate and easy to realize industrial production.
[0028] 4) The present invention utilizes a "sandwich structure" of mixed rubber sheets in coordination with a step-by-step vulcanization process to improve the vulcanization effect of solid rubber tires. The first step utilizes high-temperature vulcanization to improve the fluidity of the rubber and reduce the defects of the load-bearing tires. The second step utilizes low-temperature vulcanization to completely vulcanize the rubber without causing a decrease in mechanical properties due to over-sulfurization, thereby ensuring that the product obtains the best vulcanization uniformity, and the molded solid rubber tire has excellent mechanical properties, thereby further improving the service life of the natural rubber road wheel solid tire. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a digital photo of the high modulus graphene oxide / natural rubber uniformly cured solid load-bearing tire molded in Example 1. DETAILED DESCRIPTION
[0030] The present invention is further described below in conjunction with specific embodiments.
[0031] The raw materials used in the examples are all conventional commercially available raw materials.
[0032] Table 1 Test standards used for performance characterization
[0033]
[0034] A high modulus graphene oxide / natural rubber, prepared from natural rubber, reinforcing filler carbon black and graphene oxide, an activator, a softener, an antioxidant, an antioxidant, a vulcanization accelerator, a vulcanizing agent, and an interface modifier;
[0035] The specific formula is:
[0036]
[0037]
[0038] Example 1
[0039] An efficient preparation process for a high modulus graphene oxide / natural rubber uniformly cured solid load-bearing tire comprises the following steps:
[0040] (1) Weigh 50 g of 10 mg / mL graphene oxide (GO) slurry, add 50 g of deionized water, and ultrasonicate at 200 W for 15 min to obtain a 5 mg / mL graphene oxide uniform aqueous dispersion;
[0041] (2) Weighing 166.7 g of natural rubber latex with a solid content of 60 wt.%, adding the graphene oxide uniform aqueous dispersion obtained in step (1), and mixing thoroughly to obtain a uniformly dispersed mixed emulsion; adding 60 g of a 10 wt.% CaCl2 solution to the mixed solution to demulsify the raw rubber, washing, dehydrating, and drying to obtain a graphene oxide / natural rubber masterbatch;
[0042] (3) placing the graphene oxide / natural rubber masterbatch obtained in step (2) in an internal mixer, mixing at 110° C. for 4 min, adding 2 g of antioxidant 2,2,4-trimethyl-1,2-dihydroquinoline polymer, 2 g of antioxidant N-(1-methylisopentyl)-N'-phenyl-p-phenylenediamine and 2 g of vulcanization accelerator N-(oxydiethylene)-2-benzothiazolesulfonamide in sequence, and continuing to mix for 4 min; adding 85 g of carbon black, 5 g of interface modifier Si69, 5 g of activator ZnO and 2 g of softener stearic acid and continuing to mix for 4 min, discharging the rubber after mixing evenly; after the rubber is cooled to room temperature, transferring it to an open mixer for mixing at 60° C., adding 2 g of sulfur during the mixing process, mixing evenly for 6 min, and then thinning until there are no bubbles in the rubber to obtain a high modulus graphene oxide / carbon black / natural rubber mixed rubber and pressing it into a 5 mm thick film;
[0043] (4) placing the graphene oxide / natural rubber masterbatch obtained in step (2) in an internal mixer, mixing at 110° C. for 4 min, adding 2 g of antioxidant 2,2,4-trimethyl-1,2-dihydroquinoline polymer, 2 g of antioxidant N-(1-methylisopentyl)-N'-phenyl-p-phenylenediamine and 2 g of vulcanization accelerator N-(oxydiethylene)-2-benzothiazolesulfonamide in sequence, and continuing to mix for 4 min; adding 85 g of carbon black, 5 g of interface modifier Si69, 5 g of activator ZnO, and 2 g of softener stearic acid and continuing to mix for 4 min, discharging the rubber after mixing evenly; after the rubber is cooled to room temperature, transferring it to an open mixer for mixing at 60° C., adding 2 g of sulfur during the mixing process, mixing evenly for 15 min, and thinning until there are no bubbles in the rubber to obtain a high-viscosity graphene oxide / carbon black / natural rubber mixed rubber and pressing it into a 0.3 mm thick film;
[0044] (5) placing the high modulus graphene oxide / carbon black / natural rubber mixed rubber sheet obtained in step (3) between the upper and lower high viscosity graphene oxide / carbon black / natural rubber mixed rubber sheets obtained in step (4) to form a "sandwich structure" mixed rubber, and making a rubber strip with a width of 30 mm after standing for 20 hours;
[0045] (6) Coating the surface of the metal hub of the road wheel with adhesive Chemlock 205 and drying it, and then wrapping the "sandwich structure" adhesive strip prepared in step (5) around the surface of the metal hub, with a wrapping thickness of 30 mm;
[0046] (7) The metal wheel hub wrapped with the "sandwich structure" rubber strip obtained in step (6) is placed in a road wheel mold and vulcanized in steps at 15 MPa. The first step uses high-temperature vulcanization at 160°C for 4 minutes, and the second step uses low-temperature vulcanization at 145°C for 26 minutes to obtain a uniformly cured solid load-bearing tire of high modulus graphene oxide / natural rubber.
[0047] Example 2
[0048] An efficient preparation process for a high modulus graphene oxide / natural rubber uniformly cured solid load-bearing tire is exactly the same as that in Example 1, except that the amount of graphene oxide dispersion with a concentration of 10 mg / mL added in step (1) is 100 g.
[0049] Example 3
[0050] An efficient preparation process for a high modulus graphene oxide / natural rubber uniformly cured solid load-bearing tire is exactly the same as that of Example 1, except that the amount of sulfur added in steps (3) and (4) is 2.5 g.
[0051] The performance test results of Examples 1-3 are shown in Table 2.
[0052] Comparative Example 1
[0053] An efficient preparation process for a uniformly cured solid load-bearing tire of natural rubber is exactly the same as that of Example 1, except that graphene oxide is not added.
[0054] Comparative Example 2
[0055] An efficient preparation process for a graphene oxide / natural rubber uniformly cured solid load-bearing tire is exactly the same as that of Example 1, except that no interface modifier is added.
[0056] Comparative Example 3
[0057] A highly efficient preparation process for a graphene oxide / natural rubber solid load-bearing tire is the same as that of Example 1, except that step (4) is omitted and a rubber strip made of a high modulus graphene oxide / carbon black / natural rubber mixed rubber sheet is used instead of a rubber strip made of a "sandwich structure" mixed rubber sheet in Example 1 to be bonded and wound around a wheel hub.
[0058] Comparative Example 4
[0059] An efficient preparation process for a solid load-bearing tire of graphene oxide / natural rubber is the same as that of Example 1, except that a step-by-step vulcanization process is not used in step (7), and a conventional vulcanization process is used, with a vulcanization pressure of 15 MPa, a vulcanization temperature of 150° C., and a vulcanization time of 30 min.
[0060] The performance test results of Comparative Examples 1-4 are shown in Table 2.
[0061] Table 2 Performance test results of Examples 1 to 3 and Comparative Examples 1 to 4
[0062]
[0063] It can be seen from Table 2 that the solid road wheel rubber tire prepared by the present invention has the characteristics of high hardness, high modulus, low dynamic heat generation, excellent mechanical properties, etc. In addition, it can also be seen from Table 2 that by using two reinforcing fillers, carbon black and GO, in combination with in-situ interface modification to improve their compatibility with the NR matrix, thereby improving the dispersion of the reinforcing filler in the rubber matrix, the hardness and mechanical properties of the rubber can be effectively improved. In addition, during the vulcanization stage of the load-bearing tire, the present invention uses a "sandwich structure" mixed rubber sheet to make a rubber strip that is attached to the wheel hub and combined with a step-by-step vulcanization process to enable the product to obtain the best uniformity of vulcanization degree, so that the molded solid rubber tire has excellent mechanical properties, thereby further improving the service life of the natural rubber road wheel solid tire.
[0064] The above is only a specific implementation of the present invention, which enables those skilled in the art to understand or implement the present invention. Although detailed descriptions are given with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments, and they should all be covered by the protection scope of the claims.
Claims
1. An efficient preparation process for a high modulus graphene oxide / natural rubber uniformly cured solid load-bearing tire, characterized in that: The high modulus graphene oxide / natural rubber is made of the following raw materials in the following weight ratios: 100 parts of natural rubber, 40-120 parts of carbon black, 0.5-5 parts of graphene oxide, 1-20 parts of activator, 1-20 parts of softener, 1-10 parts of antioxidant, 1-10 parts of antioxidant, 1-20 parts of vulcanization accelerator, 1-20 parts of vulcanizing agent, and 1-20 parts of interface modifier; The preparation process comprises the following steps: (1) adding deionized water to graphene oxide slurry, and obtaining a uniform aqueous dispersion of graphene oxide by ultrasonic dispersion; (2) adding the graphene oxide uniform aqueous dispersion obtained in step (1) to natural rubber latex, and stirring and mixing them thoroughly to obtain a uniformly dispersed mixed emulsion; adding a flocculant to break the emulsion to obtain raw rubber, washing, dehydrating, and drying to obtain a graphene oxide / natural rubber masterbatch; (3) The graphene oxide / natural rubber masterbatch obtained in step (2) is placed in an internal mixer for internal mixing at 110-120°C, and carbon black, interfacial modifier, antioxidant, antioxidant, vulcanization accelerator, activator and softener are added in sequence. After internal mixing for 5-12 minutes, the rubber is discharged and cooled to room temperature. The rubber is then mixed on an open mixer at 50-80°C for 6-15 minutes, and a vulcanizing agent is added. After mixing evenly, the rubber is thinned until there are no bubbles in the rubber to obtain a high modulus graphene oxide / carbon black / natural rubber mixed rubber and pressed into a film; (4) The graphene oxide / natural rubber masterbatch obtained in step (2) is placed in an internal mixer at 110-120°C for internal mixing, and carbon black, interfacial modifier, antioxidant, antioxidant, vulcanization accelerator, activator and softener are added in sequence. After internal mixing for 5-12 minutes, the rubber is discharged and cooled to room temperature. The rubber is then mixed on an open mixer at 50-80°C for 15-25 minutes, and a vulcanizing agent is added. After mixing evenly, the rubber is thinned until there are no bubbles in the rubber to obtain a high-viscosity graphene oxide / carbon black / natural rubber mixed rubber and pressed into a film; (5) placing the high modulus graphene oxide / carbon black / natural rubber mixed rubber sheet obtained in step (3) between the upper and lower high viscosity graphene oxide / carbon black / natural rubber mixed rubber sheets obtained in step (4) to form a "sandwich structure" mixed rubber, and after standing for a certain period of time, forming a "sandwich structure" rubber strip having a width smaller than the width of the metal hub; (6) Apply adhesive to the surface of the metal hub of the road wheel and let it dry, then wrap the "sandwich structure" rubber strip prepared in step (5) around the surface of the metal hub, with the wrapping thickness being the designed thickness of the rubber layer of the road wheel; (7) The metal wheel hub wrapped with the "sandwich structure" rubber strip obtained in step (6) is placed in a road wheel mold and vulcanized in steps, with the first step being vulcanization at high temperature for time C and the second step being vulcanization at low temperature for time D, to obtain a uniformly cured solid load-bearing tire of high modulus graphene oxide / natural rubber.
2. The efficient preparation process of a high modulus graphene oxide / natural rubber uniformly cured solid load-bearing tire according to claim 1, characterized in that: The interface modifier is selected from at least one of Si69, Si75, Si75-ES and Si264.
3. The efficient preparation process of a high modulus graphene oxide / natural rubber uniformly cured solid load-bearing tire according to claim 1, characterized in that: The vulcanization accelerator is N-tert-butyl-2-benzothiazole sulfenamide, N-cyclohexyl-2-benzothiazole sulfenamide or N-(diethylene oxide)-2-benzothiazole sulfenamide; the antioxidant is 2,6-di-tert-butyl-4-methylphenol, 2,2,4-trimethyl-1,2-dihydroquinoline polymer or 2-thiol benzoimidazole; the antioxidant is N-(1-methylisoamyl)-N'-phenyl-p-phenylenediamine, p-phenylaniline or dilauryl dipropionate sulfide; the activator is zinc gluconate, zinc oxide or magnesium oxide; the softener is stearic acid, dibutyl titanate or dioctyl adipate; and the vulcanizing agent is sulfur or sulfur monochloride.
4. The high modulus graphene oxide / natural rubber and the efficient preparation process of the uniformly cured solid load-bearing tire according to claim 1, characterized in that: In step (1), the power of the ultrasonic dispersion is 100-300 W, the time of the ultrasonic dispersion is 5-20 min, and the concentration of the obtained graphene oxide uniform aqueous dispersion is 2-6 mg / mL.
5. The efficient preparation process of high modulus graphene oxide / natural rubber uniformly cured solid load-bearing tire according to claim 1, characterized in that: The mass ratio of the graphene oxide in step (1), the rubber solids in the natural latex in step (2), and the carbon black, interfacial modifier, antioxidant, antioxidant, vulcanization accelerator, activator, softener and vulcanizer in step (3) is 0.5~5:100:40~120:1~20:1~10:1~10:1~20:1~20:1~20:1~20:1~20.
6. The high modulus graphene oxide / natural rubber uniformly cured solid load-bearing tire efficient preparation process according to claim 1, characterized in that: The mass ratio of the graphene oxide in step (1), the rubber solids in the natural latex in step (2), and the carbon black, interfacial modifier, antioxidant, antioxidant, vulcanization accelerator, activator, softener and vulcanizer in step (4) is 0.5~5:100:40~120:1~20:1~10:1~10:1~20:1~20:1~20:1~20:1~20.
7. The efficient preparation process of high modulus graphene oxide / natural rubber uniformly cured solid load-bearing tire according to claim 1, characterized in that: In step (5), the thickness of the middle layer of the high modulus mixed film of the "sandwich structure" mixed film is 3-6 mm, the thickness of the upper layer of the high viscosity mixed film is 0.3-1 mm, and the thickness of the lower layer of the high viscosity mixed film is 0.3-1 mm; the stop time is 20-30 h.
8. The efficient preparation process of high modulus graphene oxide / natural rubber uniformly cured solid load-bearing tire according to claim 1, characterized in that: In step (6), the adhesive is a general adhesive selected from at least one of Chemlok 6125, Chemlok 205 and Chemlok 6150.
9. The efficient preparation process of high modulus graphene oxide / natural rubber uniformly cured solid load-bearing tire according to claim 1, characterized in that: In step (7), the vulcanization pressure is 10-25 MPa, the first step vulcanization temperature is 150-170°C, the vulcanization time C is 2-6 min, the second step vulcanization temperature is 140-150°C, and the vulcanization time D is 10-30 min.
Citation Information
Patent Citations
Method for preparing graphene masterbatch by water-phase synergistic coagulation process and forming long-service-life loading wheel tire of heavy vehicle
CN114591545A